Therapeutic Endoscopic Retrograde Cholangiopancreatography (ERCP): A Single Centre 5-Year Experience - Michael Tendean; Toar D. B. Mambu; Ferdinand Tjandra; Billy Salem; Jimmy Panelewen; Everly Corputty (e-CliniC, 2023)
Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) and related procedures are established as necessary techniques in the diagnosis and treatment of biliopancreatic diseases. Caution is needed due to the high risk of complications that can be fatal. The main complications are pancreatitis, bleeding, perforation, biliary stents, and lithiasis treatment issues. This study aimed to evaluate the therapeutic ERCP at Prof. Dr. R. D. Kandou Hospital between 2017-2021. This was a retrospective study using patients’ medical record data. The results obtained a total of 196 ERCP procedures performed at Prof. Dr. R. D. Kandou Hospital in that period. Variations of etiology, technical difficulties, and morbidities were recorded. The success rate of endoscopic stone extraction was 77.9 %, EPBD 10.71 %, and stenting for biliary drainage 97.3 %. Etiology varied from bile duct stone (74%); malignancies of the pancreas (8%), duodenum (2%), and periampullary (4%); Klatskin tumor (5.6%); and other malignancies (5%). Associated morbidities were melena 2%, pancreatitis 1%, and cholangitis 0.5%. In conclusion, endoscopic retrograde cholangiopancreatography is a reliable method for the diagnosis and treatment of hepatobiliary and pancreatic diseases, shown by the low incidence of morbidities and mortalities. Keywords: endoscopic retrograde cholangiopancreatography; biliopancreatic diseases